Growth of hypoplastic mitral valves in hypoplastic left heart complex and similar constellations after anatomical left superior vena cava correction - Cesnjevar, Robert; Harig, Frank; Dietz, Moritz; Alkassar, Muhannad; Waellisch, Wolfgang; Rueffer, André; Dittrich, Sven; Purbojo, Ariawan (European Journal of Cardio-Thoracic Surgery, 2021)
OBJECTIVES: Left superior vena cava (LSVC)-related obstruction of mitral inflow is a rare finding in patients with complex cardiac anomalies like hypoplastic left heart complex. We report our experience by establishing a left superior to right superior caval vein continuity (innominate vein creation by direct LSVC-right superior vena cava end-to-side-anastomosis), and coronary sinus unroofing if indicated for LSVC-related mitral inflow obstruction. METHODS: Nineteen patients (median age: 1.0 ± 0.3 years; range: 7 days-4.8 years) underwent anatomical correction of LSVC without the use of foreign material in conjunction with repair or palliation of congenital anomalies in a single centre between April 2015 and November 2019. Indications for the procedure were LSVC-related obstruction of left ventricular inflow due to a dilated coronary sinus. Additional procedures included mitral (n = 7) or atrioventricular (n = 3) valve surgery, right ventricular to pulmonary artery conduit (n = 3), first stage palliation (n = 3) or biventricular repair (n = 5) of hypoplastic left heart complex. Three patients needed secondary mitral valve replacement (n = 3). RESULTS: All LSVC or coronary sinus-related obstructions were effectively relieved. No patient died early, 2 patients died late after the procedure. One patient needed stenting of the superior vena cava below the unobstructed cephalad vein anastomosis at the former right superior vena cava-cannulation-site. Follow-up was complete and demonstrated an 89.5% survival after 2.5 ± 0.4 years. Innominate vein patency was 100% documented by echocardiography (n = 19), cardiac catheterization (n = 6) or both. Mean mitral valve z-scores before the operation were -1.7 ± 0.2 (range -3.8 to 0.3) and increased to 0.7 ± 0.2 (range -0.7 to 1.9) after LSVC repair. CONCLUSIONS: Anatomical correction by surgical creation of an innominate vein is an effective method to relieve LSVC-related obstructions and promotes mitral valvar growth. Mitral ring sizes were at least normalized after surgery at the time of discharge. Further prospective follow-up studies to evaluate the growth potential of left-sided heart structures by reporting cardiac z-scores are needed to evaluate the true impact of coronary sinus unroofing.
CRIS-Team Scopus Importer:2021-01-29
Keywords: Congenital heart disease; Hypoplastic left heart complex; Left superior vena cava; Mitral valve growth; Mitral valve z-score